Estimating total losses from parasitoids for a field population of a continuously breeding insect, cassava mealybug, Phenacoccus herreni, (Homoptera: Pseudococcidae) in Colombia, S.A. - Driesche, R.G. van; Bellotti, Anthony C.; Castillo, J.; Herrera, C.J. (1990)
A Phenaccocus herreni Cox & Williams population studied in Colombia, S.A., across a complete cassava crop cycle did not exceed 81 mealybugs/plant. P. herreni densities in Colombia were highest in the dry season, as were levels of parasitism by the encyrtids Acerophagus coccois Smith and Epidinocarsis diversicornis (Howard). Mealybug densities declined sharply during the dry season prior to the onset of rains. Stage survival among female mealybug nymphs was lowest in the third instar. Nine percent of all female first instar mealybugs survived to enter the adult stage. The combined action of the parasitoid species present caused 54.9% mortality to the host population as estimated by a new analytical method (Bellows et al. 1989).